Hepatitis E virus and Bell's palsy. (17th November 2021) - Fritz‐Weltin, Miriam; Niedermeier, Lisa; Frommherz, Estelle; Isenmann, Nora; Csernalabics, Benedikt; Boettler, Tobias; Neumann‐Haefelin, Christoph; Endres, Dominique; Panning, Marcus; Berger, Benjamin
Abstract: Background and purpose: Acute hepatitis E virus (HEV) infections have been associated with various neurological disorders, including individual cases with Bell's palsy. Nonetheless, systematic studies in the latter are lacking. Therefore, this retrospective study systematically screened a cohort of patients with Bell's palsy for an acute HEV infection. Methods: Overall, 104 patients with Bell's palsy treated in our clinic between 2008 and 2018 were identified. Serum samples were analyzed for anti‐HEV immunoglobulin (Ig)M and IgG antibodies by enzyme‐linked immunosorbent assay. Additionally, serum samples were tested for HEV RNA by polymerase chain reaction in 92 of these 104 patients presenting within the first 7 days from symptom onset. A large group of 263 healthy individuals served as controls. Results: None of the patients with Bell's palsy but two healthy controls (0.8%) had an acute HEV infection. Anti‐HEV IgG seroprevalence indicating previous infection was unexpectedly high in patients with Bell's palsy (34%) and revealed an age‐dependent increase. Conclusions: In this first systematic study, no cases of Bell's palsy in association with an acute HEV infection were identified. However, based on previous case descriptions, rare associations cannot be excluded. Therefore, large prospective multicenter studies will be necessary for conclusions that are more definitive. Abstract : This retrospective monocentric study analyzed the association of an acute hepatitis E virus (HEV) infection in 104 patients presenting with Bell's palsy. 263 healthy individuals served as controls. None of the patients with Bell's palsy, but two healthy controls (0.8%) had an acute HEV infection. Anti‐HEV IgG seroprevalence indicating previous infection was high in both patients (36%) and controls (17%) with an age‐dependent increase. In this first systematic study, no association of Bell's palsy and an acute HEV infection was found.